The phenomenon of pro‒environmental crime: criminal law and criminological aspects - Matković, Aleksandar B; Lečić, Boriša N. (Sociološki pregled, 2025)
This paper investigates the phenomenon of pro–environmental crime from both criminal law and criminological perspectives. The first part discusses the concept and basic characteristics of pro–environmental crime. In the second part, various criminal law institutions are examined in relation to pro–environmental crimes. The third part focuses on the etiological and phenomenological aspects of pro–environmental crime, including a large number of criminological and sociological theories that we tried to use to explain the crime concerned. Notably, we highlight the types of objects involved in the act of committing pro– environmental crimes, the way of prescribing such criminal offences, the legal classifications of such offences, the differentiation of pro–environmental offences based on their level of social danger, and the nature of their goals, techniques, and strategies. The paper also addresses the vigilant aspects of radical eco–activism, modern/cyber forms of pro–environmental crime, and the necessity of expanding green criminology to encompass pro–environmental crimes.